Plant Dominant Low-Protein Diet, Nutritional Status (Phase Angle) and Progression of Renal Failure: Case-Report Study - Danijela Ristic-Medic; Snjezana Petrovic; Biljana Pokimica; Marija Paunovic; Vesna Vucic (Proceedings)
Background and Objectives: High dietary protein intake can cause intraglomerular hypertension, which may result in kidney hyperfiltration, glomerular injury, and proteinuria. The quality of dietary protein may also play a role in kidney health. Several observational studies have shown that compared with protein from plant sources, animal protein is associated with an increased risk of end-stage chronic kidney disease (CKD). A plant dominant low-protein diet composed of ≥50% plant-based sources may lead to favorable changes in the gut microbiome, which can modulate uremic toxin generation and slow CKD progression, along with a reduction in cardiovascular risk. Phase angle (PhA) as a nutritional evaluation parameter is a reliable marker for estimating muscle health and quality of life scale in CKD patients. We evaluated the effect of a calorie restrictive plant dominant low-protein diet (PLADO) on the progression of renal failure and nutrition status in the patient case report. Methods: A 68-year-old female, obese (BMI 31.9 kg/m2) with CKD grades 3 presented to her primary care physicians in October 2022, changed her diet from an unhealthy Western diet to a personalized PLADO (protein 0.6–0.8 g/kg/day), caloric-restricted diet rich in fiber, according to basal metabolic rate (energy intake 1400 kcal/day) prescribed by a dietitian doctor. Liver and thyroid function and ferritin and potassium levels were within normal limits. Habitual dietary intake was estimated with a food frequency questionnaire and their body composition, and PhA was measured using a bioimpedance analysis (InBody 770; Seoul, Republic of Korea). The optimal PhA cut-off value was identified as ≤4.4 for non-dialysis patients. Results: After 3 months, serum urea, creatinine, uric acid, and glucose levels were significantly reduced, and hematological parameters and potassium levels were not significantly different. BMI, visceral fat, and total body fat % decreased, while PhA and skeletal muscle mass were stable. Conclusions: We confirmed that the PLADO diet with ≥50% plant protein can be safely recommended to patients with stage 3 CKD, as it slows down the progression of renal failure, and does not lead to a reduction in PhA. Therefore, there is a need for nephrology to include nutritional management of kidney disease in addition to the pharmacological axis.